Como a formação em esquizoanálise e a reduçao de danos transmutam a vida e a prática clínica - Diello, Maria Luiza (2019)
This approach composes my research work for the dissertation of Academic Master’s Degree in Psychology / UFSM, having as methodological reference, cartography and, theoretical, the fields of schizoanalysis, philosophy of difference and Foucaultian thought. It accrues from some problematizations: what are we doing in this planet? What is the purport of being here, for me, for the Other, for the community and for the planet? What is the use of what we are living for? Who are the living people in whose lives I live and live within my life? What agency operates in harm way, in our lives? Thus, I understand that life must be made to function in new registers, in other directions. I work – in the clinical, institutional and social fields – with agency life in other and different lives, not with the pathways that are mine, but with the pathway of each one, with the quaint composition of his life; I notice how cartographically constitutes what is individual, that is, how a history of itself is produced, the writing of itself and how is the composition of the multiplicities. I take the agency of enunciation of Harm Reduction (DR) as an intercessor in the production of subjectivation processes in the Contemporaneous, surpassing the territorial perspective proposed by the dominant thought of prohibitionist tracing and provoking the aesthetic production of existential territories marked by other forms of being and doing life happens, going through the clinical field and the various agencies in the health. Looking at the cartographies of lives whose existential territories were affected and influenced by DR and Schizoanalysis as agencies of territorialized subjectivities, if we problematize the dominant modes of subjectivation – which sequester / capture desires, wills and subjectivities; taking as reference the deployment in people’s life in my clinical, institutional and social work as a psychologist, we see the processes triggered by these intercessors operating in the contemporaneous. I take DR as a possibility of affections production and influences, reverberation / ritornello in people's lives, production of networks, intensities, inventiveness, rhizomatic production and, in turn, movement, displacement; and in three dimensions, they are: clinical-political method, paradigm of the National Policy of Integral Attention for Users of Alcohol and Other Drugs and, as Way of Life and care production. Thus, thinking about Schizoanalysis and DR, as territorial agency in the production of subjectivation processes and clinical practice, calls us to be willing to think and live experiments, taking the former as a reading of practically everything that happens in the world and, the second, as a rupture zone in the field of care, which produces territorialization agencies, modifying practices and ways of thinking about relationships with life, as well as clinical practice.